Edukasi Tentang Asupan Protein Serta Pemeriksaan Status Gizi Lansia - Abimanyu Birawa (Lembaga Pengembangan Kinerja Dosen, 2024)
Balanced nutritional intake plays an important role in the long-term nutritional status and health of the elderly. To increase nutritional information on protein intake in the elderly and measure the nutritional status of the elderly. This activity was carried out at Posyandu Kenanga, Genjeng Weru Village, Sukoharjo Regency and involved 20 elderly people aged 45-60 years. Nutrition education for the elderly uses leaflets and checkpoints as well as measuring nutritional status based on body weight and height, then calculating body mass index or BMI to determine nutritional status. Based on the results of the pre and post test, elderly knowledge increased before and after being given nutrition education. The most common category of nutritional status in the elderly is obesity. This is not directly proportional to the pre and post test results which show that the average level of knowledge of elderly people is in the good category. It can be concluded that education and assessment of nutritional status are very important because they can improve the health status of the elderly.